Challenges to achieving a successful hospitality internship program in Malaysian Public Universities - Soffi, Muhammad Nazreen Ezyan; Mohamad, Siti Fatimah; Che Ishak, Farah Adibah (Macrothink Institute, 2020)
Researchers have recognized the benefits and importance of having successful internship programs for all relevant stakeholders; students, universities and employers. Despite these significances, internship is found to be provocative as previous studies revealed the challenges perceived by undergraduates and employers. Nonetheless, researchers underlook the challenges perceived by internship coordinators in terms of placement, assessment and cooperation given by undergraduates and employers. Hence, the purpose of this study was to explore the challenges to achieving a successful internship program in the hospitality industry. The findings derived from seven internship coordinators in public universities that offered hospitality degree programs throughout Malaysia. The data obtained from semi-structured interviews were analyzed using thematic analysis. Seven themes were extracted as the challenges of this study, namely- 1) attitude, 2) constraint, 3) manipulation, 4) placement, 5) sexual harassment, 6) expectation, and 7) student preparedness. The findings of this study are expected to give insights to all relevant stakeholders, in terms of improvement and strategies needed in designing an internship program, particularly in the hospitality industry. Besides, it is anticipated to guide internship coordinators and students to well-prepare for the expected difficulties that they might experience while coordinating and undergoing the internship process.